Uji Kadar Protein, Pati Dan Antosianin Tepung Ubi JalarUngu Yang Dimodifikasi Dengan Penambahan Sari Buah Nanas Dan Lama Fermentasi - Kurniawati, Betty Ayu; , Dra. Suparti, M.Si (2015)
Modification flouris potato flour fermented using lactic acid bacteria This research aimed to determine the effect of pineapple juice with different concentrations and long fermentation on protein content, starch and modified starch anthocyanins from purple sweet potato. Kind of research is experimental research with the treatment of various concentration of pineapple juice and fermentation time. This research used a completely randomized design (CRD) using the two treatments, the concentration of pineapple juice and fermentation time, each treatment consisted of two replicates. The first treatment is N0 (without pineapple juice), N1 (50% pineapple juice), N2 (62.5% pineapple juice) and N3 (pineapple juice 75%) as a treatment concentration of pineapple juice. Each treatment is fermented for A1 (12 hours) and A2 (24 hours) at a temperature on 40C. The results showed that the variation of pineapple juice and fermentation time a different effect on the levels of starch modification purple sweet potato. Treatment N3A1 highest starch content (75% pineapple juice and fermentesi 12 hours) with 85,08%. While the addition of pineapple juice and fermentation time has no effect on protein content and anthocyanin modification purple sweet potato flour. N3A1 highest protein content (75% pineapple juice and fermentation 12 hours) with a mean of 5.18 mg / g. The highest levels of anthocyanins levels N0A1 (without pineapple juice and fermentation 12 hours) with a mean of 106.59 mg / L.